تنمية القدرات الابتكارية للعاملين كمدخل لتحسين أداء نظم الإنتاج بالمنظمات الصناعية - النحاس، محمد نبيل إبراهيم Alnahhas, Mohammed Nabil Ibrahim (جامعة عين شمس - كلية التجارة, 2022)
تمثل الهدف العام للبحث في تحديد أثر تنمية القدرات الابتكارية والمتمثلة في (الطلاقة، الحساسية، المرونة، الأصالة)، كمدخل لتحسين أداء نظم الإنتاج بالمنظمات الصناعية الغذائية، قام الباحث بالاعتماد على المنهج الوصفي التحليلي في البحث وتم اختيار ثلاث منظمات وهم (جهينة، وإيديتا، وعبورلاند)، وتمثلت العينة في 317 من العاملين المسؤولين عن الإنتاج بهذه المنظمات، توصلت النتائج إلى أن المنظمة تضع في اعتبارها أحداث التعاون المستمر بين جميع الإدارات، كما تحرص على فتح التعاون بين المنظمات الأخرى لتطوير الأداء ونقل التكنولوجيا والمعرفة المتطورة، والتعرف على المعلومات والحلول عبر شبكة الابتكار وتنمية قدرات العاملين الابتكارية، كما تحرص على الوصول للخبراء داخل الشبكة الابتكارية والتواصل معهم، وتتسم بالمرونة الكافية لجعل جميع العاملين لهم الحق في مشاركة عمليات اكتساب المعارف، والتكنولوجية الخارجية لتنمية قدراتهم، واتباع نظام مكافآت للعاملين الداعمين لتنمية قدرات العاملين الابتكارية، وتتبع نظام قوى لتقييم مهارات المتقدمين للوظائف الشاغرة لتنمية قدراتهم الابتكارية، وتمثلت الإضافة العلمية للبحث في أن تنمية القدرات الابتكارية للعاملين لها اثر كبير على أداء نظم الإنتاج. The general objective of the research was to determine the impact of developing innovative capabilities represented in (fluency, sensitivity, flexibility, originality), as an entry point to improve the performance of production systems in food industrial organizations. and Obourland), and the sample represented 317 workers responsible for production in these organizations. The results concluded that the organization takes into account the events of continuous cooperation between all departments, and is keen to open cooperation between other organizations to develop performance, transfer technology and advanced knowledge, and identify information and solutions through a network. Creativity and the development of the innovative capabilities of workers, and it is also keen on reaching experts within the innovative network and communicating with them, and is flexible enough to make all workers have the right to participate in the processes of acquiring knowledge, and external technology to develop their capabilities, and following a system of rewards for workers supporting the development of workers’ innovative capabilities, and following a strong system for evaluating workers’ innovative capabilities. The skills of applicants for vacant jobs to develop their innovative capabilities, and the scientific addition to the research was that the development of The innovative capabilities of employees have a significant impact on the performance of production systems.
Keywords: المؤسسات الصناعية -- القدرات الابتكارية -- الإنتاج الغذائي -- التنمية المهنية